Peran Pekerja Sosial Dalam Pelayanan Orang Dengan Gangguan Jiwa Terlantar Di Yayasan Mentari Hati Kota Tasikmalaya - Lilis Karwati; Nastiti Novitasari; Herdina Feby Syafitri (JPUS: Jurnal Pendidikan Untuk Semua, 2021)
Realizing that there are many people who suffer from neglected mental disorders, most of them are not taken care of and treated even they are excluded from society, ostracized and shunned when in fact people with neglected mental disorders need special attention and need help from the surrounding environment. The purpose of this study is to determine the role of social workers in social services for people with neglected mental disorders, restoring people with mental disorders and providing empowerment to people with mental disorders in order to give them confidence to return to society. The research method used is a qualitative method with a descriptive approach through observation, interviews, and documentation. The data analysis technique used is through four stages of data analysis which includes data collection, data reduction, data presentation and verification. The results showed that the social workers at the Mentari Hati foundation had performed the roles of social workers well, namely as a facilitator, broker, mediator, defender and protector which was carried out at the Mentari Hati foundation. So the conclusion from this research is that all the roles of social workers have been running well, further enhance all the roles of social workers to develop the potential skills, and competencies that social workers already have. Keywords: Role, Social Worker, Mental Disorders.